Two anomalies in a population of Longidorus sp. (Nematoda: Longidoridae) from Serbia - Barsi, László (Biologia Serbica, 2021)
Two anomalies in a population of Longidorus sp. from Serbia have been described and illustrated. Several females and males had extra odontostyles, and one female had extra odontostyle and two vulvae.